Optimizing Super Kampung Chicken Semen Quality: Impact of Holding Frequency on Macroscopic and Microscopic Attributes - Anggriani, Yolah; Pagala, muhammad amrullah; Auza, Fuji Astuty; Sandiah, Natsir (Pascasarjana Universitas Halu Oleo, 2024)
The advantages of super Kampung chickens include a faster growth period and robust body resistance to diseases. The success of artificial insemination (AI) in poultry is influenced by various factors, such as the holding technique, storage frequency, spermatozoa concentration, male productivity, inseminator skills, insemination time, and reproductive quality. This study aimed to evaluate the impact of holding frequency on the macroscopic and microscopic quality of chicken semen. The research design employed was a completely randomized design (CRD) consisting of three treatments and five replications. The treatments included P1 (semen storage once per week), P2 (semen storage twice per week), and P3 (semen storage three times per week). Data analysis was conducted using ANOVA, and in case of a significant e ffect, the least significant difference test (LSD) was performed. The results indicated that semen storage did not have a significant effect (P>0.05) on the macroscopic quality (volume, consistency/thickness, semen pH, color, and odor) of semen from super Kampung chickens. Furthermore, different semen storage frequencies did not significantly impact (P>0.05) spermatozoa movement and motility percentage, but had a substantial effect (P